Pro-export policy of the Czech Republic (with focus on activities of CzechTrade and CzechInvest) - Koschantová, Klára; Sato, Alexej, 1952-; Petříček, Václav, 1944-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2013)
My bachelor thesis deals with the pro-export policy of the Czech Republic. The first part is devoted to export promotion policies and institutions through which this support is implemented. In the second part, I took a closer look primarily at two of these institutions, namely CzechTrade and CzechInvest, whose work I will try to analyze and evaluate. Based on this work, I would like to verify whether the current market support is sufficient, and to evaluate whether this support is implemented correctly and effectively. In conclusion I also mention the planned merger of these agencies.
Vedoucí práce: Alexej Sato
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses